Energy Efficient Load Balanced Multipath Routing in MANET (International Journal of Engineering and Computer Science, 2018)
A mobile ad hoc network is defined as a collection of mobile nodes where each node is free to move arbitrarily. As wireless network expands in size, complexity and demand, effective and uniform distribution of the traffic load in the entire network is a matter of utmost importance. In situations, when an intermediate node is used for longer duration for forwarding packets, it may cause traffic concentration on it resulting in higher latency and depletion of battery power of nodes. In this paper, we have studied the problem of load balancing in multi-hop ad-hoc networks and an algorithm ELB-AOMDV is devised to incorporate load balancing mechanism into a multi hop multi path routing protocol (AOMDV) for achieving better load distribution over nodes in a network.